Feeding habits of the american crocodile, Crocodylus acutus (Cuvier, 1807) (Reptilia: Crocodylidae) in the Southern Coast of Quintana Roo, México. - Villegas, Alejandro; Schmitter-Soto, Juan Jacobo (Instituto de Ecología, A.C., 2008)
Between January and September 2006, 21 crocodiles (Crocodylus acutus) were captured and six were recaptured in four lagoons located in the southern coast of Quintana Roo. Stomach contents were obtained in order to identify prey items, which were analyzed by the frequency and volume method. In decreasing order of importance, prey items were fish, crustaceans, birds, mammals and insects. Diet of crocodiles changed considerably according to their body size. Adult crocodiles added larger preys (birds and mammals) to their diet; fish and crustaceans were present in the diet at all sizes, thus showing theimportance of these prey in the diet of American crocodiles.